Barriers to Effective Implementation of Edutainment in the Classroom - Abdul Wahid Zaini; Brett Aaron Huggins; Rahmat Prasetyo (Al-Qalam Institue, 2024)
This research explores the challenges faced in implementing edutainment in elementary schools as an alternative method for increasing student motivation and involvement and honing their problem-solving skills. This research is based on the increasing need to create an engaging and effective learning atmosphere and problems related to low student motivation and monotonous learning methods. The research method used is a qualitative approach with the type of case study research. Data collection techniques are carried out through in-depth interviews with teachers, direct observation in the classroom, and documentation of learning activities. The findings show that although edutainment succeeds in increasing student engagement, the main challenge is balancing the entertainment element and the educational objectives. In addition, efficient time management and selecting appropriate educational games are key in optimizing the benefits of edutainment. The contribution of this research is to provide insight into how the implementation of edutainment can be optimized at the elementary school level, as well as identify obstacles that need to be considered by educators. The recommendation of this study is to create the right balance between entertainment and learning and to provide training to teachers to choose and apply educational games that are relevant to the learning objectives.